Enabling selective aerobic oxidation of alcohols to aldehydes by hot electrons in quantum-sized Rh nanocubes. (December 2018) - Dai, Xinyan; Rasamani, Kowsalya Devi; Wu, Siyu; Sun, Yugang
Abstract: Selective aerobic oxidation of primary alcohols to aldehydes at low temperature and ambient condition is essential for many value-increasing industrial processes, although the low oxidizing power of the ambient oxygen represents the major challenge to widely implement this important reaction. Herein, we report that the oxidizing power of oxygen adsorbed on quantum-sized Rh nanocubes is significantly enhanced upon photo-illumination to accelerate the oxidation reaction with a selectivity of 100%. Light absorption in the Rh nanocubes anchored on large silica spheres leads to efficient generation of hot electrons in the Rh nanocubes, which are injected into the O–O bonds adsorbed on Rh surface to cleave them into adsorbed oxygen atoms with a much higher oxidizing power. The silica (SiOx ) spheres enhance both the light absorption power and colloidal stability of the small Rh nanocubes, making the Rh/SiOx hybrid particles as a unique photocatalyst to readily promote the selective aerobic oxidation of alcohols to aldehydes. Graphical abstract: Highlights: Hot electrons promote dissociation of adsorbed oxygen molecules. Surface oxygen atoms enable selective oxidation of alcohols. Quantum-sized Rh nanocubes benefit hot electron injection. Silica nanospheres enhance light absorption of Rh nanocubes.